Complement regulation: physiology and disease relevance - Heeyeon Cho (Korean Pediatric Society, 2015)
The complement system is part of the innate immune response and as such defends against invading pathogens, removes immune complexes and damaged self-cells, aids organ regeneration, confers neuroprotection, and engages with the adaptive immune response via T and B cells. Complement activation can either benefit or harm the host organism; thus, the complement system must maintain a balance between activation on foreign or modified self surfaces and inhibition on intact host cells. Complement regulators are essential for maintaining this balance and are classified as soluble regulators, such as factor H, and membrane-bound regulators. Defective complement regulators can damage the host cell and result in the accumulation of immunological debris. Moreover, defective regulators are associated with several autoimmune diseases such as atypical hemolytic uremic syndrome, dense deposit disease, age-related macular degeneration, and systemic lupus erythematosus. Therefore, understanding the molecular mechanisms by which the complement system is regulated is important for the development of novel therapies for complement-associated diseases.